2014
DOI: 10.1039/c4ra09859e
|View full text |Cite
|
Sign up to set email alerts
|

Composite banded core and non-banded shell transition patterns in stereocomplexed poly(lactide acid) induced by strongly interacting poly(p-vinyl phenol)

Abstract: Banded cores and non-banded shells with transitional patterns in stereocomplexed poly(lactic acid) sc-PLA (PLLA : PDLA ¼ 1 : 1) interacting with amorphous poly(p-vinyl phenol) (PVPh) (20-30 wt%) were investigated by using polarized optical (POM), atomic force (AFM), and scanning electron microscopy (SEM). The central core of the spherulites is ring-banded, which transitions into non-banded patterns on the outer peripheral in sc-PLA/PVPh blends crystallized at T c ¼ 160-180 C. This composite crystal morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Further examination revealed the different types of spherulites shown in Figure 8(c-e). Ni'mah et al 32 reported a similar type of lamellar pattern for the spherulites of PLA. Specifically, the circular fibrous texture of the lamellae leads to the formation of a circular ring within the periphery of the spherulites.…”
Section: Evaluation Of Lamellar Arrangements Of Pla-tec In Presence Omentioning
confidence: 79%
See 1 more Smart Citation
“…Further examination revealed the different types of spherulites shown in Figure 8(c-e). Ni'mah et al 32 reported a similar type of lamellar pattern for the spherulites of PLA. Specifically, the circular fibrous texture of the lamellae leads to the formation of a circular ring within the periphery of the spherulites.…”
Section: Evaluation Of Lamellar Arrangements Of Pla-tec In Presence Omentioning
confidence: 79%
“…A completely different type of lamellar pattern of the spherulite, a scattered lamellar pattern, is observed in Figure 8(e). Ni'mah et al 32 reported a similar type of lamellar pattern for the spherulites of PLA. Both the POM and the SEM observations revealed that these different types of spherulites have different lamellar arrangements.…”
Section: Evaluation Of Lamellar Arrangements Of Pla-tec In Presence Omentioning
confidence: 79%
“…1 The fact that the morphology of a highly diluted scPLA [such as poly(p-vinyl phenol) or other interacting amorphous polymers] has a highly dendritic structure of dual patterns composed of a ring-banded dendritic pattern in the core center and a nonbanded dendritic pattern in the outer rim region enclosing the banded core has been proven earlier. 41 The highly asymmetric nonracemic PLLA/PDLA = 98/2, 94/6, and 90/10 can in reality be regarded as a "highly diluted" scPLA dispersing in a large quantity of excess PLLA chains. Thus, naturally, the excess PLLA, upon holding at T c = 140 °C for long enough time, grows from these fibrous crystal tips and starts to aggregate along the straight dendrites, finally packing into a sword-blade shape with a diamond-lozenge tip, as shown in Figure 9B.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some studies have reported blends of PLLA and other materials, such as blends of PLLA with other crystalline polymers, i.e. PLLA with poly(ethylene oxide (PEO) (Lee et al, 2012); PLLA with poly(D-lactic acid) (PDLA) (Ni'mah et al, 2014); PLLA with other amorphous polymers, i.e. PLLA with atactic poly(methyl methacrylate) (aPMMA) (Woo et al, 2014); PLLA with poly(vinyl phenol) (PVPh) (Ni'mah et al, 2014); PLLA with elastomeric polymers such as natural rubber (Desa et al, 2016;Nofar et al, 2019); PLLA with nanoparticles (Raquez et al, 2013); PLLA with biodegradable and biomaterial such as chitosan (Duarte et al, 2010) or cellulose (Ni'mah et al, 2017); and PLLA and plasticizers (Sitompul et al, 2016).…”
Section: Introductionmentioning
confidence: 99%